China's Public Diplomacy to Build a Positive Image among The Muslim Community in Indonesia - Hasbi Aswar; Muhammad Zulfikar Rakhmat; Muhammad Habib Pashya (Dialogia: Islamic Studies and Social Journal, 2022)
To carry out economic and political expansion in various countries, China has also exerted various public diplomacy efforts to maintain its image. Indonesia as one of the most important destinations is not an exception. This research aims to analyze various strategies adopted by China to sustain its positive image among Muslims in Indonesia. This study uses a qualitative method using the conceptual framework of public diplomacy. Data were collected from primary and secondary sources on the Indonesian government, the Chinese government, as well as Muslim groups in Indonesia from 2000 to 2019. This research shows that China, during the Xi Jinping era, has actively been carrying out public diplomacy activities specifically directed toward Muslims in Indonesia through official representatives, educational and cultural institutions, and Confucius Institutes.